Anesthesia for patients with malignant hyperthermia and those at risk: case report (Brazilian Journal of Health Research, 2024)
Introduction: Malignant hyperthermia (MH) is a pharmacogenetic clinical syndrome that, in its classic form, occurs during anesthesia with the use of drugs that trigger the MH crisis, such as halogenated drugs or the depolarizing neuromuscular blocker - succinylcholine. It was defined as an autosomal dominant inheritance, with more than 210 mutations in the ryanodine receptor (RYR1) in skeletal muscle. Case report: With the present case report and current bibliographic review, the objective is to describe the safe anesthetic technique used in a patient susceptible to MH and to make some considerations. The procedure was performed at the Hospital Universitário Cassiano Antônio Moraes (HUCAM/UFES), with adequate preparation of the perioperative environment. Conclusion: This article serves as a foundation for preparing a safer and more suitable environment for anesthetic management of patients susceptible to MH or with a confirmed diagnosis.
Keywords: Malignant hyperthermia; Halogenated; Succinylcholine; Pre-anesthetic preparation; Perioperative environment